EKLEKTISITAS DAYAH DAN SEKOLAH VOKASI DALAM BINGKAI FILSAFAT PENDIDIKAN KONTEMPORER - Yuni Setia Ningsih (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
Digitalization as well as globalization disturbs the identity of this nation in general and the younger generation in particular. The impact of digitalization and globalization is like a flood that is difficult to stop. The younger generation prefers to follow a hedonic lifestyle. Society needs a generation that still has an identity. Identity as a pious Muslim. Apart from this identity, they also have good IT skills. To be a good Muslim, there is a dayah institution. To become an IT expert, there is a vocational school. Therefore, it is necessary to analysis to meet the needs of the community theoretically and philosophically regarding the two institutions. This study aims to analyze contemporary philosophical views (conservatism, liberalism, and criticism) and how to solve these problems.This research is a library research with a descriptive approach. Based on the research data, it was found that the views of schools were different. Some are compatible and some are not. Some reinforce each other, some contradict each other. From the point of view of contemporary educational philosophy, especially conservatism, liberalism, and criticism, it is necessary to have a combination or eclecticity between the two institutions. So that the demands of society can be met.